Thermal Comfort Study of Outdoor Space for Face-to-Face Learning System: Study of Outdoor Thermal Comfort for Face-to-face Learning Systems - Maria Rosita Maharani; Eddy Prianto (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2022)
The transmission covid-19 virus is through droplets are splashed by people who have the virus. Therefore, activities that make crowding especially in closed rooms with poor air circulation are very avoided, because the rate of transmission in the inner room with poor air circulation has a higher presentation compared to transmission in the outside room. With new protocol to use maximum room capacity limit of 50%, using outdoor space can be good alternative solution to increase space for face to face learning system. But there is needed a study of thermal comfort for outdoor space. The object taken as a sample in this study was sitting area of the Undip Architect campus. This paper present measurements of dry temperature, humidity, and air movement with quntitative method. From the examine of effective temperture show that the object research have cozy thermal comfort according by Mom dan Wiesebron standards. This examamination of effective temperature can also be exam for other outdoor environments.